Echa romansu tradycyjnego w twórczości literackiej Ignacego Krasickiego = Echoes of traditional romance in the literary output by Ignacy Krasicki - Siama, Alfred (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article concerns the attitude of the outstanding writer of the Polish Enlightenment, Ignacy Krasicki, to the epic pre-bildungsroman genre, which is romance. The research attention in the article was focused on the opinions about romances expressed in several literary works of the prince bishop.
Keywords: Krasicki, Ignacy (1735-1801); romans tradycyjny; oświecenie; krytyka; traditional romance; Enlightenment; criticism